Hamas och Gazaremsan - Om folkrättslig legitimitet och status - Kvarfordt,Erik (2018)
The conflict between the government of the Gaza strip and Israel re-emerged in 2006 when Hamas won the election and went on to seize control of the region in 2007. Since then the conflicts between Hamas and Israel, as well as between Hamas and al-Fatah, has characterized the politics and everyday life in the region. This paper discusses the status of Hamas in international law and asks the question whether Hamas is a legitimate representative of the Palestinian population in Gaza and, if not, what it would take for them to become legitimate. The paper starts with discussing what it is that defines a state, what it means to be a state, in the context of rights and obligations, the right to self-determination for peoples and what other entities, that does not constitute states but still hold international legal personality, there are. Finally, it examines the conflict between Hamas and Israel and, in short, discusses how the past 20 years has changed the situation in the region. This paper concludes that international recognition is decisive for the legitimacy of Hamas as a representative for the Palestinian population in Gaza and that it is mainly for political reasons that a recognition by the international community has not yet occurred. It discusses the problems surrounding recognition and what the continued refusal to recognize the Hamas government might mean. The principle of self-determination is not clearly defined in international law and questions remain as to when a people has this right and what the right means in different circumstances. The principle does not state an obvious right to secession from an existing state. The paper also asks the question as to whether it is evident to regard Palestine as one aspiring state with one people or if there might be room under the principle of self-determination to regard different claims as equally legitimate.
Keywords: Folkrätt; legitimitet; erkännande; Gazaremsan; Hamas